Requirements for information professionals in a digital environment: some thoughts - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2009)
Purpose - The purpose of this paper is to point out the increasing need to provide information professionals with a sound grounding in the technological aspects of their profession. Design/methodology/approach - The paper sets out by describing the sudden increase in volumes of information that confront our society, and then looks at how the younger generation approaches/uses this mass of information. It then analyses how the traditional functions of information professionals (presentation of material, reliable preservation of information, maintaining authenticity, and conservation) are handled in an electronic environment. Findings - The paper discovers that considerable technical knowledge and experience are required to carry out those same functions in an electronic environment and suggests a redefinition of information sciences as information engineering. Research limitations/implications - The paper recommends increasing the technology content in the training of information professionals such as archivists, records managers and librarians. Originality/value - The paper concludes with a radical assertion that the proper locus for such training is a school of engineering rather than a school of librarianship, information studies and/or archives.
Keywords: Archives management; Libraries; Information science; Records management; Information profession; ARCHIVAL EDUCATION